SELEKSI ISOLAT FUSARIUM BERDASARKAN PADA BERBAGAI SUMBER KEMAMPUAN TUMBUH KARBON SEBAGAI PENGINDUKSI PEMBENTUKAN GAHARU Gyrinops versteegii (Gilg) Domke - , I Gde Adi Suryawan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Various agar media were used for stimulating conidia production and promoting the growth of Fusariumsp as bio-induction agent on G. versteegii (Gilg) Domke,. The aims of the study were: 1) To select Fusarium spp. Isolated from G. versteegii (Gilg) Domke that could induce gaharu production